Robert J. answered • 07/07/13

Certified High School AP Calculus and Physics Teacher

Johnny R.,

Great observation!

You can use integer function to get a recursive form.

3, 9 , -1, -4, -15

t(1) = 3

t(n) = t(n-1) * [int(n/2)+2], if n is even.

t(n) = t(n-1) - [int(n/2)+9], if n is odd.

Check:

t(1) = 3

t(2) = 3*(1+2) = 9

t(3) = 9 - (1+9) = -1

t(4) = (-1)*(1+4) = -4

t(5) = (-4) - (2+9) = -15

t(6) = (-15)(3+2) = -75

t(7) = -75 - (3+9) = -87

t(8) = (-87)(4+2) = -522

......

Peter G.

Hi Jonny.

This makes sense except for the fact that the multiplier should be "6" for this line as "5" has already been used:

-87 x

5 = -522 (multiplication, increasing multiplier by 1)should be

-87 X 6 = -522Thus the remainder of the problem needs to be adjusted.

07/07/13